Accurate color imaging of pathology slides using holography and absorbance spectrum estimation of histochemical stains. Issue 3 (19th November 2018) - Zhang, Yibo; Liu, Tairan; Huang, Yujia; Teng, Da; Bian, Yinxu; Wu, Yichen; Rivenson, Yair; Feizi, Alborz; Ozcan, Aydogan
Abstract : Holographic microscopy presents challenges for color reproduction due to the usage of narrow‐band illumination sources, which especially impacts the imaging of stained pathology slides for clinical diagnoses. Here, an accurate color holographic microscopy framework using absorbance spectrum estimation is presented. This method uses multispectral holographic images acquired and reconstructed at a small number (e.g., three to six) of wavelengths, estimates the absorbance spectrum of the sample, and projects it onto a color tristimulus. Using this method, the wavelength selection is optimized to holographically image 25 pathology slide samples with different tissue and stain combinations to significantly reduce color errors in the final reconstructed images. The results can be used as a practical guide for various imaging applications and, in particular, to correct color distortions in holographic imaging of pathology samples spanning different dyes and tissue types. Abstract : An accurate colorization method for holographic imaging of pathology slides is presented. Color accuracy is significantly improved after applying the absorbance spectrum estimation of histochemical stains. This work provides a solution to the color inaccuracy problem of holography.